Pengaruh Pendapatan Nasional terhadap Tingkat Kemiskinan di Indonesia dalam Perspektif Ekonomi Syariah - Noni Diah Agustin; Salsabila Ramadhani; Adiva Rizqy Ayudia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the influence of national income, as measured by Gross Domestic Product (GDP), on poverty levels in Indonesia from a sharia economic perspective. The research method used is quantitative with a simple linear regression approach, supported by a literature review to enrich the analysis from an Islamic perspective. The data used is annual secondary data from the 2010-2023 period sourced from the Central Statistics Agency (BPS). The results indicate that national income (GDP) has a negative and significant effect on poverty levels in Indonesia, meaning that every increase in GDP is followed by a decrease in the percentage of the poor. From a sharia economic perspective, national income growth must be accompanied by a fair distribution mechanism through zakat, infaq, sedekah, and waqf (ZISWAF) instruments so that its benefits can be felt by all levels of society, in line with the concepts of falah and maqashid sharia.